2011
DOI: 10.1007/s13361-011-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Fragmentation of Radical Peptide Anions: Insights from Vacuum Ultra Violet Spectroscopy

Abstract: We have studied the photodissociation of gas-phase deprotonated caerulein anions by vacuum ultraviolet (VUV) photons in the 4.5 to 20 eV range, as provided by the DESIRS beamline at the synchrotron radiation facility SOLEIL (France). Caerulein is a sulphated peptide with three aromatic residues and nine amide bonds. Electron loss is found to be the major relaxation channel at every photon energy. However, an increase in the fragmentation efficiency (neutral losses and peptide backbone cleavages) as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 47 publications
(66 reference statements)
3
37
0
Order By: Relevance
“…29 To assess the optical properties of radical protein anions, we also combined a laser (Nd 3+ :YAG laser, time duration 5 ns, 4th harmonic λ = 266 nm, repetition rate 20 Hz, 20 mJ/pulse) to the synchrotron radiation in a two-color scheme. 26,27 The two photon beams were spatially combined via a drilled-coated mirror located ∼30 cm upstream of the ion trap entrance. The UV laser light was reflected at 90 • by the coated mirror and injected collinearly to the axis of the ion trap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 To assess the optical properties of radical protein anions, we also combined a laser (Nd 3+ :YAG laser, time duration 5 ns, 4th harmonic λ = 266 nm, repetition rate 20 Hz, 20 mJ/pulse) to the synchrotron radiation in a two-color scheme. 26,27 The two photon beams were spatially combined via a drilled-coated mirror located ∼30 cm upstream of the ion trap entrance. The UV laser light was reflected at 90 • by the coated mirror and injected collinearly to the axis of the ion trap.…”
Section: Methodsmentioning
confidence: 99%
“…2 We used electron photodetachment to report the first electronic excitation spectra of polypeptides, 22,23 and of a protein in vacuo, 24 and demonstrated the feasibility of UV spectroscopy on large isolated biomolecular ions. 25 Electron emission following VUV excitation of peptides and proteins was recently reported, 26,27 opening the route for VUV spectroscopy of large proteins in the gas phase. In this paper, we explore the photo-induced electron detachment of protein polyanions in the 6-16 eV VUV range.…”
Section: Introductionmentioning
confidence: 99%
“…Ion spectroscopy (typically undertaken as a type of photodissociation action spectroscopy) has been covered in a number of excellent reviews and will not be included in depth here. 2732 …”
Section: Introductionmentioning
confidence: 99%
“…Electron photodetachment spectroscopy has been probed further in the VUV for carulein, a sulfated peptide, melittin and insulin using the coupling of the LTQ XL and a VUV beamline described in part II.B.3.2. Electron detachment remained the main relaxation channel in the 4.5–20 eV range (Brunet et al, ). Observation of resonances on the photodetachment yields, which correspond closely to electronic transitions reported for peptides (Serrano‐Andrés & Fülscher, ), indicated that the two steps photophysical model for photodetachment was still valid in an extend wavelength range.…”
Section: Photoactivation Of Multiply Deprotonated Biological Ions: Elmentioning
confidence: 99%
“…Observation of resonances on the photodetachment yields, which correspond closely to electronic transitions reported for peptides (Serrano‐Andrés & Fülscher, ), indicated that the two steps photophysical model for photodetachment was still valid in an extend wavelength range. Investigations on the doubly deprotonated carulein (a sulfated peptide) revealed that the main fragmentations were a 7 , a 8 , and a 9 ‐sequence ions accompanied by abundant tryptophan, CO 2 and SO 3 losses from the oxidized species (Brunet et al, ). The fragmentation pattern did not evolve much in the 5.5–20 eV range.…”
Section: Photoactivation Of Multiply Deprotonated Biological Ions: Elmentioning
confidence: 99%